2013 IEEE 26th International Conference on Micro Electro Mechanical Systems (MEMS) 2013
DOI: 10.1109/memsys.2013.6474258
|View full text |Cite
|
Sign up to set email alerts
|

Temporary wafer bonding and debonding by an electrochemically active polymer adhesive for 3D integration

Abstract: Thin wafer handling is an important issue in 3D integration technologies. This paper reports on an efficient method for bonding a thin wafer and debonding it at room temperature from a carrier wafer. This method addresses the major problem of fragility and flexibility in handling of thin wafers used in TSV fabrication. In the presented method the carrier wafer is spin coated with an electrochemically active polymer adhesive. It is then bonded to a device wafer. The wafer stack is thinned and finally released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…26,27 Recently, we have shown debonding on Al-coated Si substrates using the ElectRelease polymer. 28 In another study related to voltage-assisted polymer bonding with Cytop/PMMA, the influence of an applied voltage during bonding on the bond strength was evaluated and it was shown that very high voltages lead to reduced bond strength. However, the involved voltages are much higher than the voltages used for the ElectRelease polymer and different physical mechanisms are involved.…”
mentioning
confidence: 99%
“…26,27 Recently, we have shown debonding on Al-coated Si substrates using the ElectRelease polymer. 28 In another study related to voltage-assisted polymer bonding with Cytop/PMMA, the influence of an applied voltage during bonding on the bond strength was evaluated and it was shown that very high voltages lead to reduced bond strength. However, the involved voltages are much higher than the voltages used for the ElectRelease polymer and different physical mechanisms are involved.…”
mentioning
confidence: 99%